Study of Parathyroid gland function in normal pregnant women in Tikrit city - Mossa M. Marbut; Mena D. Mustafa; Jawad A. Salih (Journal of Madenat Alelem University College, 2017)
Background: During pregnancy, there an increase in calcium demands to helps building of fetus’s skeleton, to met this demands the parathyroid gland secretes parathyroid hormone to maintain calcium homeostasis. Aim of study: is determine the function of parathyroid gland and calcium turnover during pregnancy in normal healthy pregnant women in Tikrit city. Subjects and methods: A longitudinal follow up study was conducted in Ibn-Rushed health care center at Tikrit city. The study was done from the 15th of November 2016 to the end of March 2017. Thirty healthy pregnant women was participated in the present study, aged from 18 to 40 years in their 15–18th week of pregnancy. All pregnant women were followed up every month, about 5 ml of venous blood was drawn from the pregnant women every four weeks till the end of the 2nd trimester or the beginning of 3rd trimester. The blood lifted to clotted then centrifuged to separate the serum. The separated serum kept in deep freezing, until collection of all samples to be used in hormone and biochemical analysis. Results: PCV and Hb shows a highly- significant difference (P ≤ 0.01) among these three followed-up months. There is a highly-significant difference (P ≤ 0.01) in serum PTH in the three followed-up months. Prolactin concentrations were significantly higher during the second trimester, in other hand there is no-significant difference in serum osteocalcin concentration between the first trimester as compare with the second trimester (P > 0.05). Serum calcium and phosphors shows a no-significant difference (P > 0.05) in the three followed-up month of 30 pregnant women. Magnesium shows a significant difference (P ≤ 0.05) in the results of the three-follow-up month, while in ALP there is a highly-significant difference (P ≤ 0.01) in the results, the highest value in the 5th month.